Nanoscale Memristor: Great potential for memory and synapse emulator for computing applications - Luís, Joana Cristina Marques (2020)
This work reports the fabrication and electrical characterization of Metal-Insulator-Metal (MIM) devices for neuromorphic applications using zinc-tin-oxide (ZTO) and indium-gallium-zinc-oxide (IGZO) as the switching layers and molybdenum (Mo) for the devices ‘contacts. A lithographic mask was used along with physical vapor deposition (PVD) processes for the production of the different samples’ layers. Using ZTO as a switching layer in order to replace other elements that are becoming scarce such as indium or gallium is of relevant importance, therefore it was first attempted a ZTO based MIM device. Upon electrical characterization the ZTO devices show an analog behavior without the need of current compliance (being therefore self-limited), good multilevel storage property, reliability and a stable state retention for long periods of time. It is suspected a 2D type of switching mechanism, based on the tunneling through a Schottky barrier at the interface, however the details of the exact mechanism aren’t yet clear. Furthermore, the device is highly prone to interact with humidity present in the atmosphere and some fabrication steps, which is a possible explanation for the anticlockwise RESET. A second batch of ZTO devices was fabricated in order to remediate the RESET process, using a passivation step, however the RESET direction wasn’t affected although the rectification properties of the devices were enhanced. Since upon pulse testing the ZTO devices behaved erratically, this switching layer was discarded and IGZO used instead. With this alternative amorphous oxide semiconductor material, the symmetry and linearity of the conductance change was evaluated and transition from STP (Short-Term Potentiation) to LTP (Long-Term Potentiation) successfully demonstrated upon pulse repetition, showing similar decay fashion to human memory, following a Kohlrausch-Williams-Watts function (commonly called “stretched-exponential function”).